Pengaruh Electronic Word Of Mout Keputusan Pembelian Produk Scarlett Whitening Pada Marketplace Shopee : Pengaruh Electronic Word Of Mouth Dan Lifestyle Terhadap Keputusan Pembelian Produk Scarlett Whitening Pada Marketplace Shopee (Studi Kasus Pada Mahasiswa Fakultas Ekonomika Dan Bisnis Universitas Majalengka) - Deni Istiono. MM; Nining Kurniasih (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Abstract. Increasingly sophisticated technological developments indirectly impact consumer lifestyles and behavior when making purchasing decisions online. The more businesses competing in the same field, the more careful and intelligent consumers will be in choosing products that suit their needs and desires. Purchase decisions made by consumers describe how far marketers are in trying to market a product to consumers. This study aims to determine the effect of electronic word of mouth and lifestyle on purchasing decisions for Scarlett Whitening products on the Shopee marketplace. The method used in this study is a survey method with a descriptive analysis approach and verification analysis. The population in this study were students of the Faculty of Economics and Business, University of Majalengka with a total sample of 100 respondents. The sampling technique used is incidental sampling. The data collection used is by distributing questionnaires using a Likert scale measurement. The data analysis used is multiple linear regression analysis, and the coefficient of determination is first tested by classical assumptions and then tested by the hypothesis. The results of this study indicate that partially electronic word of mouth has a positive and significant effect on purchasing decisions. This means that the better electronic word of mouth is given, the higher the level of decision to purchase Scarlett Whitening products on the Shopee marketplace. Lifestyle has a positive and significant effect on purchasing decisions. This means that the better the lifestyle is, the higher the level of decision to purchase Scarlett Whitening products on the Shopee marketplace. Keywords : Electronic Word Of Mouth, Lifestyle, Purchase Decision